Resilience, hope and flourishing are inversely associated with burnout among members of the Society for Gynecologic Oncology - Monica Hagan Vetter; Matthew K. Vetter; Jeffrey Fowler (Elsevier, 2018)
Purpose: In this study we sought to: 1) determine rates of burnout and other associated indices of psychosocial distress such as alcohol and substance abuse, 2) establish the baseline performance of gynecologic oncologists on several positive psychology metrics, 3) determine if increased hope, resilience, and flourishing are associated with decreased burnout. Methods: A survey of members of the Society of Gynecologic Oncology (SGO) was conducted in spring of 2017. Participants were sent an electronic questionnaire consisting of 82 items measuring burnout, depression, substance abuse, flourishing, resilience, hope, and psychological wellbeing. Results: A total of 1745 members were invited and 374 (21.4%) responded. Overall, 23.0% of respondents scores above clinical cutoffs indicating burnout. Almost 50.0% of participants screened positive for depression, 17.0% screened positive for alcohol abuse and 12.0% screened positive for substance abuse. Respondents meeting criteria for burnout were more likely to screen positive for depression (p < .001) and substance abuse (p < .001). Participants not meeting criteria for burnout had higher resilience, flourishing, hope, and wellbeing scores (p < .001). Male respondents had higher levels of hope, resilience, and wellbeing while married participants had higher flourishing and wellbeing scores than their unmarried counterparts. Parents had higher levels of resilience and wellbeing compared to non-parents. Conclusion(s): Burnout and associated indices of physiological distress continue to affect a large segment of SGO membership. Participants not meeting the criteria for burnout had higher scores on resilience, flourishing, hope, and wellbeing metrics. This suggests new targets for evidence-based interventions to mitigate burnout among members of SGO. Keywords: Burnout, Resilience, Flourishing, Wellbeing